Joseph's Platz - Redaway, James (engraver):::Creator::::::::::::; Batty, Robert, 1789-1848 (artist):::Contributor:::::::::::: (London; published by Rodwell & Martin, printed by M. Queen)
Engraving of the Josefsplatz in Vienna